Mapping the intersection of ethics, AI, and higher education: a bibliometric approach - Gunadi, Rustian Akbar; Robandi, Babang (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This bibliometric study systematically maps the intersection of ethics, artificial intelligence (AI), and higher education using data sourced from the Scopus database and analyzed through bibliometric tools such as VOSviewer and CiteSpace. The analysis reveals a notable increase in publication trends since 2019, with major contributions from Springer Nature and leading institutions such as University College London and the University of Oxford. Keyword co-occurrence analysis identifies central themes such as